Role of Financial Indicators and Firm Characteristics in Determining Firm Value - Jatmiko, Fattah Rahman; Aminah, Siti (Universitas Dian Nuswantoro Semarang, 2025)
Market value reflects investor confidence in a company’s future performance. A higher market value suggests stronger growth potential and, correspondingly, indicates a greater level of shareholder wealth. Consequently, understanding the factors that influence company value is important. This study seeks to provide empirical evidence regarding the influence of financial performance and company-specific characteristics on company value. This study focuses on companies listed on the Indonesia Stock Exchange (IDX) in the transportation and logistics sector for the period 2021–2023. A total of 48 data observations were eligible for analysis. The results of the study reveal that financial performance indicators, as proxied by profitability and leverage, do not influence company value. In contrast, company-specific characteristics, as proxied by company size, positively influence company value.